Target-mediated drug disposition pharmacokinetic-pharmacodynamic model of Bosentan and Endothelin-1 - Volz, Anke-Katrin; Haefeli, Walter E. (Clinical pharmacokinetics, 2017)
Background and ObjectivesBosentan is a competitive antagonist on endothelin receptor A and B (ETA and ETB), displacing the endogenous binding partner endothelin-1 (ET-1) from its binding sites. After administration of escalating single doses of 10-750 mg as an intravenous (i.v.) infusion, bosentan showed dose-dependent pharmacokinetics (PK). The aim of this analysis was to develop a PK model of bosentan after i.v. administration including competitive antagonism with ET-1 and to analyze its influence on blood pressure and heart rate with a combined pharmacokinetic/pharmacodynamic (PK/PD) model.MethodsPK/PD data from 70 young male Caucasian subjects were analyzed after single i.v. administration of 10, 50, 250, 500, and 750 mg of bosentan. Population analyses, simulations, and evaluation were performed using a non-linear mixed-effects modeling approach.ResultsThe PK of bosentan was best described by a two-compartment, target-mediated drug disposition (TMDD) model. ET-1 plasma and urine profiles were successfully integrated into the bosentan two-compartment, TMDD model encompassing competition for the same receptor. A multiple-peak phenomenon of bosentan plasma concentrations after i.v. administration was best described by a diurnal expression or reappearance of ET receptors on the cell surface. Blood pressure was best described by an E max model; heart rate was modeled as a compensatory effect of changes in blood pressure.ConclusionThe developed competitive PK/PD model of bosentan and ET-1 after i.v. administration provides a first step towards understanding the complex PK properties of bosentan and offers a valuable tool for future PK/PD research.
Published online: 11 April 2017
Gesehen am 30.07.2018